Surgical intervention for feeding and nutrition difficulties in cerebral palsy: a systematic review. (5th June 2013) - Ferluga, Elizabeth D; Sathe, Nila A; Krishnaswami, Shanthi; Mcpheeters, Melissa L
<x xml:space="preserve">Abstract</x> Aim The aim of the study was to systematically review surgical intervention for feeding difficulties in cerebral palsy. Method We searched databases including MEDLINE from 1980 to July 2012. Two reviewers independently assessed studies and rated the overall quality and strength of the evidence. Results Thirteen publications (11 unique studies) met the inclusion criteria and addressed gastrostomy outcomes or treatment of reflux via fundoplication. In nine studies, gastrostomy‐fed children gained weight. Relative to typically developing populations, baseline weight z‐scores ranged from −3.56 to −0.39 and follow‐up z‐scores ranged from −2.63 to −0.33. Other growth measures were mixed. Two studies assessed fundoplication: in one, both Nissen fundoplication and vertical gastric plication reduced reflux (by 57% and 43% respectively), while in one case series, reflux recurred within 12 months in 30% of children. The highest rates of adverse events across studies were site infection (59%), granulation tissue (42%), and recurrent reflux (30%). Death rates ranged from 7 to 29%; however, the underlying cause was probably not surgery. Interpretation Evidence for the effectiveness of surgical interventions is insufficient to low. Studies of gastrostomy typically demonstrated significant weight gain. Results for other measures were mixed. Many children remained underweight, although, given a lack of appropriate reference standards, these results should be interpreted cautiously.